C1 CAGE detects transcription start sites and enhancer activity at single-cell resolution - Tsukasa Kouno (Nature Portfolio, 2019)
Single-cell transcriptomic profiling allows the exploration of cellular heterogeneity but commonly focuses on the 3′-end of the transcript. Here the authors introduce C1 CAGE, which detects the 5′ transcript end in a multiplexed microfluidic system.